Path Analysis on the Biopsychosocial and Economic Determinants of Quality of Life in Patients with Type II Diabetes Mellitus: Evidence from Surakarta, Central Java - Nurvitasari, Rahsunji Intan; Tamtomo, Didik Gunawan; Dewi, Yulia Lanti Retno (Journal of Epidemiology and Public Health, 2020)
Background: Type 2 diabetes mellitus (DM) is a chronic disease that is increasing to an alarm